Thermal equilibrium as a predictor of growth efficiency in preterm infants - Heiter, Julia; Konow, Juliane; Koch, Jochim; Singer, Dominique; Ebenebe, Chinedu Ulrich (Frontiers in Pediatrics, 2024)
Introduction: Providing adequate nutrition to preterm infants to achieve postnatal growth similar to intrauterine growth remains challenging due to the unpredictability of individual determinants. Material and Methods: We used a calculation program for infant incubators to compare the estimated heat balance with the caloric intake and growth rate in Very Low Birth Weight Infants (VLBWI). Results and Discussion: A group of 32 VLBWI was studied over a period of 14-28 days. An interrelationship between thermal equilibrium and growth rate was observed, with standardized incubator settings being unable to avoid periods of negative thermal balance and concomitantly poor growth rate. Conclusion: Determining personalized incubator settings by means of a calculation program could help improve nutrition and growth in preterm infants.